Post-graduate training in Internal Medicine: the generalist and sub-specialisation - Poças, José (2000)
After a short introduction, the author describes apersonal view of the different possible aspects ofInternal Medicine. A definition, historicalperspective, organisation, vocation and formation,with reference to the different realities in the USA(where these problems have been much discussed)and Portugal, including several well-known expertcitations, is made. The dichotomy between GeneralInternal Medicine and its Sub – Specialities, as wellas the relation between the General Internist andthe Specialist is elaborated. Special emphasis is givento the priority need of future investment in PrimaryCare and in the formation of Generalists (Internists,Paediatricians and Family Physicians who are inshort supply in our country) on which,unquestionably, our Health System must be based.Also attention is drawn to the undesirable numberof General Physicians without suitable formationand institutional employment. A plan to differenciateInternal Medicine as a Medical Speciality, basedon a common period of 3 years, is presented andjustified. The division of General Internal Medicineinto three different but complementary fields issuggested: Primary Care Internist, HospitalSpecialist and Emergency Specialist, adapting therecognised American and German models. The finalconclusions emphasise the need to face theseproblems with determination and coherence, puttingpatients suffering and the way Health System works,as our top priority.